Causes and effects of Accident at Construction Site: A Study for the Construction Industry in Bangladesh - Ahmed, Shakil (International Journal of Sustainable Construction Engineering and Technology, 2020)
Accident at construction site has shaped a horrific figure of death for every year in Bangladesh. This study aims to identify and rank the causes and effects of accident at construction projects in Bangladesh. The study also discusses the characteristics of top-ranking causes and effects. Various direct and indirect linkage of top causes and effects are also analyzed in this study. A widespread literature review and interviews with experts take place to identify the causes and effects of construction accident and design the questionnaire. The questionnaire-based survey was used to elicit the perception of construction professionals towards causes and effects of accident at construction site. This study has identified 77 causes under 14 major groups and 22 effects of accident and ranked them based on Relative Importance Index (RII). The top 5 causes of accident are: unaware of safety-related issue, lack of personal protective equipment, lack of safety hazards eliminating design, unfit equipment, and lack of knowledge and training on equipment respectively. The major 5 effects of accident are: loss of human lives, demotivation of workers/reduce morale, conflict with workers, loss of productivity of project, and delay in work progress respectively. This study will help the project participants and authorities to know and understand the various characteristics and linkage of causes and effects of construction accidents to improve the safety management in the Bangladeshi construction industry. It contributes to the body of knowledge, as it reveals for the first time the causes and effects of accident in the Bangladeshi construction industry.